2022
DOI: 10.17776/csj.983869
|View full text |Cite
|
Sign up to set email alerts
|

Searching for New Natural Inhibitors of Acetylcholinesterase Enzyme

Abstract: History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The apricot seed extracts exhibited notable inhibitory effects on the enzyme acetylcholinesterase, which is responsible for the conversion of acetylcholine to choline. According to the study's findings, apricot seed extract in ethanol could take the place of a prescription medication for neurodegenerative diseases [93]. According to a different study, amygdalin can decrease fibroblast cells and inhibit the transforming growth factor TGF β1 [94].…”
Section: Nutritional Valuementioning
confidence: 99%
“…The apricot seed extracts exhibited notable inhibitory effects on the enzyme acetylcholinesterase, which is responsible for the conversion of acetylcholine to choline. According to the study's findings, apricot seed extract in ethanol could take the place of a prescription medication for neurodegenerative diseases [93]. According to a different study, amygdalin can decrease fibroblast cells and inhibit the transforming growth factor TGF β1 [94].…”
Section: Nutritional Valuementioning
confidence: 99%
“…AD is an irreversible neurological illness that causes cognitive and memory loss, mental and behavioral disorders, and language impairments, all of which can severely affect a person's social and professional life [3,4]. Studies have shown that Aβ deposition, neurofibrillary tangles, oxidative stress, cholinergic deficiency, and neuroinflammation are factors in the formation of AD [5][6][7]. To slow the progression of AD, clinical studies have used enzymes (including β-secretase and γ-secretase, which are involved in amyloid precursor protein catabolism and acetylcholinesterase, which is involved in acetylcholine catabolism) as targets to attempt drug design due to alterations in enzyme activity, which usually have definite effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Akocak and Lolak [4] evaluated antioxidant properties and cholinesterase activities of certain inhibitors. AChE inhibitors in Alzheimer's treatment aim to enhance cognitive functions by increasing synaptic acetylcholine levels [5]. Heredia-García et al [6] associated BPA effects on AChE with hormonal changes affecting nervous system functions.…”
mentioning
confidence: 99%